Human Trafficking and Migration: interview with Jacquelyn Meshelemiah - Pereira, Cláudia (OEm Conversations With, 2019)
Interview with Jacquelyn Meshelemiah Dr. Jacquelyn C. A. Meshelemiah is a Licensed Social Worker (LSW). She earned her Bachelor of Science in Social Work (BSSW), Master of Social Work (MSW), and Doctorate (PhD) from the College of Social Work, of The Ohio State University, USA. Dr. Meshelemiah has taught numerous courses across the curricula, but now exclusively teaches Assessment & Diagnosis in Clinical Social Work Practice, as well as Human Trafficking. She is the author and co-author of numerous publications, such as “Human Sex Trafficking” and, her latest, “Human Rights Perspectives in Social Work Education and Practice”. Has also done a series of presentations and trainings at the university, local, national, and international levels. Her primary research agenda centers on social justice, human rights, and anti-trafficking work. She has a cross-comparative analysis of human trafficking in Ghana, Uganda, Ethiopia, England, Mexico, Canada, Costa Rica, and the United States.